Over the Rim : the Parley P. Pratt exploring expedition to Southern Utah, 1849-50 - Smart, William B. (William Buckwalter), 1922-2018; Smart, Donna Toland, 1923- (Utah State University Press, 1999)
Over the Rim is the first book about an important but little-known expedition sent by Brigham Young to explore southern Utah. Led by Mormon apostle Parley P. Pratt, the party traveled from Salt Lake City south across the rim of the Great Basin to the Virgin River near future St. George. They brought back to Mormon leaders their first detailed portrait of the country to the south that the church planned to settle. By 1849, the new Mormon settlement at Great Salt Lake City was taking on an air of permanence as companies of Latter-day Saints continued to arrive. Brigham Young and other leaders nee.